Contrast enhancement for medical images based on histogram equalization followed by median filter - Jagatheeswari, P.; Suresh Kumar, S.; Rajaram, M. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.